Patterning of L10 FePt nanoparticles with ultra-high coercivity for bit-patterned media. Issue 2 (13th December 2016) - Meng, Zhengong; Li, Guijun; Wong, Hon-Fai; Ng, Sheung-Mei; Yiu, Sze-Chun; Ho, Cheuk-Lam; Leung, Chi-Wah; Manners, Ian; Wong, Wai-Yeung
Abstract : Highly ordered L10 FePt nanoparticles with the record-high coercivity of 3.6 T were prepared from a single-source via one-step pyrolysis under Ar/H2 ; the organometallic precursor was also patterned on substrates for magnetic recording media using nanoimprint lithography. Abstract : L10 -ordered FePt nanoparticles (NPs) with ultra-high coercivity were directly prepared from a new metallopolyyne using a one-step pyrolysis method. The chemical ordering, morphology and magnetic properties of the as-synthesized FePt NPs have been studied. Magnetic measurements show the coercivity of these FePt NPs is as high as 3.6 T. Comparison of NPs synthesized under the Ar and Ar/H2 atmospheres shows that the presence of H2 in the annealing environment influences the nucleation and promotes the growth of L10 -FePt NPs. Application of this metallopolymer for bit-patterned media was also demonstrated using nanoimprint lithography.